2017
DOI: 10.1155/2017/2969324
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes of Cocoa Beans during Roasting Process

Abstract: During cocoa beans roasting, there are physicochemical changes that develop the chocolate quality attributes. Roasting systems have a particular influence on the development of these characteristics, and the effects of operation variables for each system must be evaluated. The objective of this study was to evaluate the effect of roasting time and temperature in a rotatory system on cocoa beans physicochemical parameters of quality as moisture, water activity, pH, total acidity, color ( * , * , * ), total phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Finally, for hue angle (h • ), a mean value of 55.12 ± 8.26 was determined with a range from 68.77 (sample 2) to 36.49 (sample 6). Other authors reported L* values quite different from those obtained in the present study, while results for parameters of a* and b* were similar [32]. The values obtained for h • were similar to those reported by Sacchetti et al [14].…”
Section: Ph Moisture and Coloursupporting
confidence: 82%
“…Finally, for hue angle (h • ), a mean value of 55.12 ± 8.26 was determined with a range from 68.77 (sample 2) to 36.49 (sample 6). Other authors reported L* values quite different from those obtained in the present study, while results for parameters of a* and b* were similar [32]. The values obtained for h • were similar to those reported by Sacchetti et al [14].…”
Section: Ph Moisture and Coloursupporting
confidence: 82%
“…In Table 1 [46]. The decrease of TPC is associated with the thermal and oxidative degradation of these compounds [35]. It was proven that, at high temperature, low molecular weight phenolic compounds easily volatilize [50].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the roasting process leads to the loss or modification of flavanols, which leads to a 14% loss of the total phenolic content (TPC), as well as the epimerization of epicatechin to catechin [25][26][27][28][29][30][31][32].Kinetic modeling can provide a deeper understanding of the changes that occur during thermal processing controlling and food quality optimization [33,34]. Since these roasting techniques were introduced to the chocolate industry, the roasting time and temperature have been studied, applying designs or models that allow for a proper assessment of the process [35]. Various studies have been reported on the effect of roasting on cocoa nibs' coloration, physical/chemical changes [4,5,8,16,23,25,36], flavor changes [37], and the kinetics of polyphenol degradation during drying [12,28,38]; however, studies on the kinetics of the polyphenol and monomeric flavan-3-ol degradation of Criollo cocoa during the roasting process are scarce, so the aim of the present study was to understand this degradation and determine the kinetic parameters.…”
mentioning
confidence: 99%
“…The dried and roasted samples (5 g) were fully dehydrated in an oven at 105°C for 24 h for determining the dry matter and the moisture content. [8] The compositions of dried and cocoa samples (water activity, pH, fat content and acidity; Table 1) were determined according to García-Alamilla et al [8]…”
Section: Moisture and Composition Determinationmentioning
confidence: 99%
“…The behavior shown in (Figure 1b) can be explained by chemical transformations during roasting, attributed to Maillard reactions, caramelization of sugars, protein degradation, and synthesis of sulfur compounds. [8] According to Domian et al [10] , the zone (a w > 0.7) is where the water is available as a solvent for low-molecular-weight solutes, wherein the material probably swells and softens, which is where saccharides dissolve; thus, the water is capable of acting as a solvent. In our case, the effect is notorious in the zone (a w > 0.81).…”
Section: Mathematical Expressionmentioning
confidence: 99%